Digital Mammography A Holistic Approach - Mercer, Claire; Hogg, Peter; Kelly, Judith; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This heavily revised second edition is a practically focused textbook focusing on how to successfully utilise mammography-related techniques. It covers a wide range of topics related to holistic mammographic imaging reflecting the emerging digital and artificial imaging technology. Furthermore, new chapters provide clear practical focused guidance on how to provide psychological and emotional support to both clients and colleagues, and the support of persons with dementia. Digital Mammography: A Holistic Approach is a concise textbook covering the latest techniques that can be applied in this field. Therefore, it is of significant interest to radiographers, technicians, technologists, physicists, and nurses seeking to improve their understanding of these techniques. Additional questions via app: Download the Springer Nature Flashcards app for free and use exclusive additional material to test your knowledge.
Mammography Screening: Philosophy -- Screening Programmes for breast cancer -- Anatomy of the Breast -- Breast Density and Influencing Factors -- Aetiology and Epidemiology -- Benign Breast Change and Malignant Disease -- Signs and Symptoms of Breast Cancer and Management Pathways -- Disease Progression -- Interval Cancers -- Mammographic Density -- Caring for Patients and Staff -- Patient Story -- Phycological considerations in attending for mammography screening -- Patient and Staff Anxiety -- Transactional Analysis -- Client practitioner interaction within breast services -- Digital Health Technology -- Pain in Mammography -- Tissue Viability and Skin Tearing -- Equipment -- Mammography Equipment -- AI in Mammography -- Radiation Dose -- Image Appraisal and Quality Control -- Radiographic service quality -- Automated PGMI -- Imaging Techniques -- Recording Information -- Infection Control -- Repetitive strain injury -- Practical Mammography -- Mammography -- Compression -- Supplementary Projections -- Magnification and Compression Views -- Specimen Imaging -- Imaging the Augmented Breast -- Imaging the Male Breast -- Imaging Bariatric, post surgical and limited mobility clients -- Imaging Persons Living with Dementia -- Interventional Procedures -- Tomosythesis -- Contrast Enhanced Investigations.
Keywords: Radiology; Internal medicine; Radiology; Radiology; Internal Medicine; Breast Neoplasms -- diagnostic imaging; Mammography; Radiography; Image Processing, Computer-Assisted; Patient Satisfaction